The factors that influence retirement confidence among women working in Segamat district's public sector Johor / Muhamad Anas Adnan - Adnan, Muhamad Anas (Faculty of Business Management, Universiti Teknologi MARA, Johor, 2017)
The aim of this research is to investigate the influence of financial literacy and financial management on retirement confidence among working women in Segamat district's public sector Johor Malaysia. A sample size of 100 respondents which mean 100 set questionnaire will be distributed to 100 women working in Segamat district's public sector. Pearson Correlational analysis to determine the relationship between the variables as the objective of this study is to determine the relationships between financial literacy, financial management and retirement confidence among women working in Segamat district's public sector. The findings reveal that financial literacy and financial management is positively correlated with retirement confidence. In addition, this study further examined the financial status, age and education background on retirement confidence. The multiple regression analysis was applied to determine the predictors of retirement confidence such as financial literacy, financial management, financial status, age and education background are significant predictors of retirement confidence among working women, with financial literacy and financial management as the major factor contributing towards retirement confidence. The main reasons to conduct this research are many previous studies have proven that women consistently perform a poor retirement confidence level compared to Men. Therefore, the goal of the research to helping working women to raise awareness of the retirement risks. This study will be use a quota sampling which means the subject are convenience chosen. Besides that, a quantitative method and primary data will be used to collect the data through survey questionnaire and secondary source such as journal, internet.